Evaluating the Performance of Two Salmon Management Strategies using Run Reconstruction. (10th February 2014) - Carney, Justin M.; Adkison, Milo D.
Abstract: Commercial salmon fisheries in Alaska are managed to obtain escapement goals within a fixed range while attempting to maximize sustained yield. Two management strategies currently being used are emergency order authority and a fixed fishing schedule. We analyzed and compared the historical performance of these two management strategies for Bristol Bay, Alaska, fisheries targeting Egegik River and Togiak River Sockeye Salmon Oncorhynchus nerka . To accomplish this, we reconstructed the daily runs to each river through the use of catch, effort, and tower count data. Our results showed that management by emergency order openings resulted in (1) the catch of a higher percentage of returning fish, (2) less yearly variation in escapement, and (3) escapements that were always above the minimum escapement goal. A fixed fishing schedule resulted in less yearly variation in catch and a harvest rate that was spread more evenly throughout the run; the more even harvest rate likely provides better protection of substocks and the sex ratio. Emergency order authority gives a manager greater control over the fishery but requires more informative data. A fixed fishing schedule provides a more predictable catch but carries a higher risk of overharvest. Each of the two management strategies was successful and was suited to the circumstances of its fishery. Received December 7, 2012; accepted September 13, 2013 Published online February 10, 2014